2020
DOI: 10.1073/pnas.1911999117
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adult lifespan and aging rates of mortality across wild mammals

Abstract: In human populations, women consistently outlive men, which suggests profound biological foundations for sex differences in survival. Quantifying whether such sex differences are also pervasive in wild mammals is a crucial challenge in both evolutionary biology and biogerontology. Here, we compile demographic data from 134 mammal populations, encompassing 101 species, to show that the female’s median lifespan is on average 18.6% longer than that of conspecific males, whereas in humans the female advantage is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
201
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(232 citation statements)
references
References 70 publications
12
201
3
Order By: Relevance
“…Alike humans or laboratory rodents, there is compelling evidence that mammalian males in the wild display shorter lives than females (Lemaître et al 2020c), as predicted by several (and non-mutually exclusive) evolutionary theories (e.g. heterogametic sex hypothesis, mother's curse hypothesis, sex differences in life history strategies, see Austad and Fischer 2016;Marais et al 2018 for reviews).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alike humans or laboratory rodents, there is compelling evidence that mammalian males in the wild display shorter lives than females (Lemaître et al 2020c), as predicted by several (and non-mutually exclusive) evolutionary theories (e.g. heterogametic sex hypothesis, mother's curse hypothesis, sex differences in life history strategies, see Austad and Fischer 2016;Marais et al 2018 for reviews).…”
Section: Discussionmentioning
confidence: 99%
“…telomere dynamics in Seychelle warblers, Acrocephalus sechellensis, Hammers et al, 2019). In addition, while mammalian females generally live longer than males in the wild (Lemaître et al 2020c), as commonly observed in humans or laboratory rodents (Austad and Fischer 2016;Zarulli et al 2018), the exact mechanisms modulating these sex differences in survival are yet to be deciphered (Tower 2017;Marais et al 2018). In that context, the focus on wild populations can be particularly relevant as the magnitude of sex differences in lifespan is likely modulated by environmental conditions, in interaction with the sex differences in genetic background (Lemaître et al 2020c;Tidière et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier works assumed that senescence was only observable in captive populations due to the high degree of extrinsic mortality experienced by pre-senescent individuals in the wild through predation, disease, or resource shortages (Kirkwood & Rose, 1991;Bronikowski & Promislow, 2005). However, with the expansion of longitudinal studies collecting repeated measures from wild individuals, recent works have identified key insights into the selective processes driving patterns of senescence in nature (e.g., Bowen et al, 2006;Nussey et al, 2006Nussey et al, , 2008Bouwhuis et al, 2009;Schroeder et al, 2012;Zhang et al, 2015;Warner et al, 2016;Dingemanse et al, 2020;Lemaître et al, 2020). A key issue for studying senescence in wild populations is that stochastic extrinsic mortality reduces the frequency of observable individuals in older age classes, hence making it challenging to disentangle among-vs. within-individual age-dependent variation -a phenomenon known as "selective disappearance" (Nussey et al, 2008;van de Pol & Wright, 2009).…”
Section: Impact Summary (297 Words)mentioning
confidence: 99%
“…Malemale competition through combat can lead to increased somatic deterioration or damage (Bonduriansky et al, 2008). Hence, in polygynous species, strong sexual selection and intrasexual competition are thought to accelerate senescence and may lead to high mortality rates in males (Clutton-Brock & Isvaran, 2007;Bonduriansky et al, 2008;Maklakov & Lummaa, 2013;Greiner et al, 2014;Beirne et al, 2015;Tidière et al, 2015; but see Lemaître et al, 2020). Conversely, in monogamous species where sexual selection is not as intense, senescence acts similarly on both males and females (Clutton-Brock & Isvaran, 2007) or shows only moderate biases towards either sex (e.g., Lecomte et al, 2010;Froy et al, 2017;Tompkins & Anderson, 2019).…”
Section: Impact Summary (297 Words)mentioning
confidence: 99%
“…The physiological hypothesis emphasises that the interactions between sex hormones and the immune system render one sex more susceptible to infection and disease [28]. For example, in mammals, males have consistently weaker immune competence than females, and this correlates with male-biased disease prevalence, mortality, and female-biased adult sex ratio [29,30]. On the other hand, the behavioural hypothesis posits that sexual differences in behaviour may cause sex-specific exposure to pathogens [31].…”
Section: Introductionmentioning
confidence: 99%